2019
DOI: 10.3390/antibiotics8030130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Activities of First and Second-Generation Ceragenins Alone and in Combination with Antibiotics Against Multidrug-Resistant Klebsiella pneumoniae Strains

Abstract: Objectives: The ceragenins, or CSAs, were designed to mimic the activities of antimicrobial peptides and represent a new class of antimicrobial agent. The aim of this study was to comparatively investigate the antimicrobial activities of first/second generation ceragenins and various antibiotics against multidrug-resistant (MDR) Klebsiella pneumoniae, including colistin-resistant bacteria. Also, the synergistic effects of two ceragenins with colistin or meropenem were investigated with six K. pneumoniae strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Although the antibiotics/chemotherapeutics mentioned above have been recommended in the treatment of infections caused by NDM-1 producing strains, our results demonstrated that these drugs were ineffective in eradicating strains tested due to the high levels of resistance. It should be underlined that our data are in agreement with those of Ozbek-Celik et al, 38 who reported that MICs values for meropenem-resistant clinical isolates of K. pneumoniae were 0.5-32 µg/mL for CSA-13 and CSA-44 (MIC 90 , 32 µg/mL) and 0.5-16 µg/mL in the case of CSA-131 (MIC 90 , 32 µg/mL). In addition, Bozkurt Guzel et al 40 also determined the antimicrobial activity of CSA-13 against E. coli ATCC 25922 with the MIC value 4 µg/ mL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the antibiotics/chemotherapeutics mentioned above have been recommended in the treatment of infections caused by NDM-1 producing strains, our results demonstrated that these drugs were ineffective in eradicating strains tested due to the high levels of resistance. It should be underlined that our data are in agreement with those of Ozbek-Celik et al, 38 who reported that MICs values for meropenem-resistant clinical isolates of K. pneumoniae were 0.5-32 µg/mL for CSA-13 and CSA-44 (MIC 90 , 32 µg/mL) and 0.5-16 µg/mL in the case of CSA-131 (MIC 90 , 32 µg/mL). In addition, Bozkurt Guzel et al 40 also determined the antimicrobial activity of CSA-13 against E. coli ATCC 25922 with the MIC value 4 µg/ mL.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, CSAs can be considered as a new approach to eradicate MDR pathogens. 16,20,29,38,39 Moreover, bacteria are unable to achieve high levels of resistance to CSAs. It should be pointed out that ceragenins appear to be well tolerated and exhibits no degradation in the presence of bacterial and host proteases, making these properties a significant area of the antimicrobial research.…”
Section: Discussionmentioning
confidence: 99%
“…CSA-13 is the most studied ceragenin. Others, such as CSA-44, CSA-131, CSA-138, and CSA-142, 25 have been designed and tested in order to optimize antimicrobial activity and to increase the safety of use.…”
Section: Introductionmentioning
confidence: 99%
“…These processes make antibiotic-like substances diffusive inside bacterial cells, where they might then inhibit metabolic processes, protein and/or DNA synthesis, etc., leading to cell death [3,29,37]. Although combinations of different types or generations of antibiotics have shown synergistic effects [38,39], the use of an appropriate EO in combination with antibiotics against bacterial pathogens could bring advantageous alternatives to reducing the use of conventional antibiotics as well as the emergence of multidrug-resistant bacteria [40]. For instance, streptomycin and kanamycin combined with lemongrass (Cymbopogon citratus) EO exhibited synergistic or additive effect against S. Typhimurium [37].…”
Section: Discussionmentioning
confidence: 99%